2008
DOI: 10.1136/ard.2007.086884
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan inhibits expression of ADAMTS4 (aggrecanase-1) in human osteoarthritic chondrocytes

Abstract: Background:Intra-articular injection of hyaluronan (HA) has been suggested to have a disease-modifying effect in osteoarthritis, but little is known about the possible mechanisms.Objective:To investigate the effects of HA species of different molecular mass, including 800 kDa (HA800) and 2700 kDa (HA2700), on the expression of aggrecanases (ie, ADAMTS species), which play a key role in aggrecan degradation.Methods:The effects of HA species on the expression of ADAMTS1, 4, 5, 8, 9 and 15 in interleukin 1α (IL1α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
111
2
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(121 citation statements)
references
References 49 publications
7
111
2
1
Order By: Relevance
“…Previous studies investigating arthritis and OA with ADAMTS4/5 knockout mice have revealed that inhibition of ADAMTS5, but not ADAMTS4, mitigates aggrecan degradation and cartilage destruction, suggesting that ADAMTS5 has an important function in aggrecan degradation in mice (20)(21)(22). However, in human chondrocytes, ADAMTS4 is upregulated by interleukin (IL)-1, tumor necrosis factor α, oncostatin M and transforming growth factor β, indicating that ADAMTS4 functions as the primary aggrecanase in human OA cartilage (4,8,9,(23)(24)(25). The results of the present study, with regard to the mRNA expression of ADAMTS4 in human OA chondrocytes under monolayer culture, provide the first indications that OPN selectively inhibits ADAMTS4 expression, while the expression of ADAMTS5 is not affected by OPN.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Previous studies investigating arthritis and OA with ADAMTS4/5 knockout mice have revealed that inhibition of ADAMTS5, but not ADAMTS4, mitigates aggrecan degradation and cartilage destruction, suggesting that ADAMTS5 has an important function in aggrecan degradation in mice (20)(21)(22). However, in human chondrocytes, ADAMTS4 is upregulated by interleukin (IL)-1, tumor necrosis factor α, oncostatin M and transforming growth factor β, indicating that ADAMTS4 functions as the primary aggrecanase in human OA cartilage (4,8,9,(23)(24)(25). The results of the present study, with regard to the mRNA expression of ADAMTS4 in human OA chondrocytes under monolayer culture, provide the first indications that OPN selectively inhibits ADAMTS4 expression, while the expression of ADAMTS5 is not affected by OPN.…”
Section: Discussionmentioning
confidence: 83%
“…Ariyoshi et al (36) demonstrated disruptive changes in chondrocyte-matrix interactions by HA oligosaccharides, which induced matrix degradation and elevated levels of aggrecanase (ADAMTS4 and ADAMTS5) activity via the NF-κB signaling pathway. Yatabe et al (4) observed that HA2700 (2,700 kDa HA) suppressed aggrecan degradation in OA chondrocytes via the downregulation of IL-1α-induced ADAMTS4 expression through the CD44 and intracellular adhesion molecule 1 signaling pathways. These results suggested that OPN may suppress aggrecanase degradation through the direct inhibition of ADAMTS4, by enhancing the binding of CD44 to HA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The direct immune modulating properties of HA are multifaceted and may happen through CD44-and/or ICAM-1 signaling pathways. 26 With respect to CD44/HA interaction, high-and low-molecular-weight forms of HA have different effects on CD44 clustering, signaling, and downstream cellular behavior such as adhesion. 11 The molecular weight of HA has direct impact on whether pro-or anti-inflammatory effects are prominent, including crosstalk between HA-mediated signaling and the COX-2/prostaglandin pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The main mechanism through which HA prevents cartilage destruction and disease progression is thought to be its action in maintaining the viscoelastic properties of the synovial fluid [13]. In addition to this, we and others have reported that HA down-regulates the expressions of MMP (Matrix Metalloproteinase) and ADAMTS (A Disintegrin And Metalloproteinase With Thrombospondin Motifs), which are involved in the degradation of cartilage, and RANKL (Receptor Activator of NF-κBLigand), which is related to osteoclastogenesis, induced in synovial fibroblasts and chondrocytes by pro-inflammatory cytokines [14][15][16]. Moreover, intraarticular injection of HA is approved in Japan to reduce knee-joint pain in RA patients [17].…”
Section: Introductionmentioning
confidence: 99%